Religion and diplomacy: a British view from the Vatican. Issue 1 (1st January 2016) - Baker, Nigel
Abstract: Based on a long experience in the field of international relations, and particularly his last task as British Ambassador to the Holy See (2011–2016), the author advocates a need for governments to pay attention to, and better understand the role of, religion in human communities as a way to run effective internal and foreign activities. The formation of foreign affairs officials requires a more humanistic approach, which includes the comprehension of religion as a backbone for cultural identity, social engagement and human development. The lack of sensibility for the religious dimension of peoples often makes diplomatic efforts unsuccessful.